The Feasibility of Learning Media for Women's Suit Sleeve Pattern Module - Ferbyan, Sheila Indri; Arrsyi, Esty Nurbaity; Suryawati, Suryawati (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2023)
This study aims to obtain an assessment of the feasibility level of the women's suit sleeve pattern module which is reviewed from several aspects, namely; (1) based on the evaluation aspect of the module which includes aspects of the feasibility of content, language, presentation, graphics and (2) based on the characteristics needed in the module including self-instruction, self-contained, stand-alone, adaptive, user friendly. This study used the Research and Development (RD) model of the Borg and Gall model. The research started from the potential and problem stage to the product revision stage. In knowing the feasibility level of the module learning media, product validation was carried out by being tested by expert panelists and students' opinions as users of the module learning media. Data was collected using instruments in the form of mixed and closed questionnaires. This study resulted in a learning media module that was feasible to use from a feasibility test from an expert panel based on a module evaluation of 90.74%, with the highest assessment obtained in linguistic feasibility. Based on the characteristics of the module obtained, 97.42% with the highest rating obtained in 3 aspects: self-contained, stand-alone, and adaptive. The results of student opinions as users were 90.59%, with the highest assessment obtained in the module evaluation aspect. So overall, from the results of the validation of the feasibility of the learning media for the women's sleeve pattern module, it is very feasible to be used as a learning medium in the Tailoring Course because it has met the suitability based on the evaluation and the characteristics of the module.